The study of structural mechanical properties of «Kartalin» ointment - M. G. Kartalov; S. Ye. Dmitruk; V. S. Dmitruk; T. V. Romanenko (Бюллетень сибирской медицины, 2009)
In this article the structure-mechanical properties research results of «Kartalin» ointment are being cited. This ointment shows the evident treatment-preventive activity with occupational and combinational dermatosis. It has been ascertained that the «Kartalin» ointment, being under consideration, appears to be structural liquid with expressive non-Newtonian flow character that is having high viscosity (100—200 Pa/s) and high yield point (20—40 Pa) with the temperature of usage 30—40 °C, which provides long skin protection. The flow properties of the composition are sufficiently time stable, which enables good preparation quality maintenance during long-term storing.